Return On Assets, Debt To Equity Ratio, Asset Growth Dan Dividend Payout Ratio Tahun Ssebelumnya Studi Pada Perusahaan Di Jakarta Islamic Index - Rembulan Rahmadia Fitri; M. Nadratuzzaman Hosen (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2015)
Start from DPR (Dividend Payout Ratio) as the benchmark that a way to indicate how much investor could get from investing his capital on a public company. As we know that many public company in Indonesia was registered in Jakarta Islamic Index also need to share some of their profit to their investors. DPR is one of the most investor consideration before investing in stock of public company. There are financial variables that could determine DPR such as ROA, DER, asset growth, and DPR a year before. The objects of this study are companies that listed on Jakarta Islamic Index on 2009–2014 period. Selection of the samples in this study using purposive sampling method and found 10 companies fit the criteria that obtained from Indonesia Stock Exchange. This study is using common-effect-panel data regression analysis. Adjusted R-square value in this study is 72.88%. DPR t-1 is partially have significant effect positively on DPR with regression coefficient value of 0.437055. However, DER partially have no effect on the DPR. Variables that affect most on DPR is DPR t-1.